(untitled) (Fiep Bulletin - online, 2013)
The Sentinel Hospitals Project was created in 2001 by the Management of Surveillance in Health Services and has as main goal to build a network of hospitals across the country. This report aims to disseminate the actions undertaken in the service of haemovigilance, identify the problems with blood transfusions and show the importance of nurses in this area of expertise. Methodology: This is a story of lived experience, the team of haemovigilance HUOL in the period from November 2003 to July 2008. Result: The non-compliances were: incomplete requests; transported samples and inadequately identified; undue packing of blood; warming of packed red blood cells, platelets concentrate freezing, thawing of fresh plasma on benches; routine pre-prescription medicine without a prior history incident of transfusion; infusion of blood in patients exchanged, without limitation the volume of infusion; labels incomplete and / or illegible, among others. The actions taken to reduce the non-compliances were up to standard procedure manual service (POP); placed officials in three shifts of work (24h) in the storage area and distribution of the blood HUOL; provided to all nurses and sectors closed educational materials and information; biannual training for health professionals; held moments of awareness; active search of transfusion incidents, among others. Conclusion: With the training, sensitization and active search of the incidents managed to reduce transfusion problems identified, but due to high turnover of pupils in hospital and health professionals, it is difficult to adherence to the standards of haemovigilance.